Identification and physiological activity of (methoxymethyl)triphenylphosphonium chloride as a new phytotoxin isolated from Rhizoctonia solani AG-3 TB - Li, Xinchun; Hou, Huihui; Li, Bin; Guo, Shiping; Jiang, Lianqiang; Xu, Chuantao; Xie, Yunbo; An, Mengnan; Zhang, Chong; Wu, Yuanhua (Frontiers in Plant Science, 2023)
Rhizoctonia solani as a cosmopolitan fungus is the causative agent of many crop diseases and leads to significant economic losses in crop production. To explore the toxin structure and its physiological activity of R. solani AG-3 TB, high performance liquid chromatography (HPLC), infrared absorption spectrum (IR) and nuclear magnetic resonance spectrum (NMR) were required. Here, the compound (methoxymethyl)triphenylphosphonium chloride (MMC) with the molecular formula C20H20ClOP was purified and identified from R. solani AG-3 TB. The pure compound MMC treated at 20 μg/mL, 50 μg/mL, and 100 μg/mL can cause obvious necrosis on leaves, increase active oxygen species (AOS),